The therapeutic promise of ATP antagonism at P2X3 receptors in respiratory and urological disorders - Ford, Anthony; Undem, Brad (Frontiers in Cellular Neuroscience, 2013)
A sensory role for ATP was proposed long before general acceptance of its extracellular role. ATP activates & sensitizes signal transmission at multiple sites along the sensory axis, across multiple synapses. P2X & P2Y receptors mediate ATP modulation of sensory pathways & participate in dysregulation, where ATP action directly on primary afferent neurons (PANs), linking receptive field to CNS, has received much attention. Many PANs, especially C-fibers, are activated by ATP, via P2X3-containing trimers. P2X3 knock-out mice & knock-down in rats led to reduced nocifensive activity & visceral reflexes, suggesting that antagonism may offer benefit in sensory disorders. Recently, drug-like P2X3 antagonists, active in a many inflammatory & visceral pain models, have emerged. Significantly, these compounds have no overt CNS action & are inactive versus acute nociception. Selectively targeting ATP sensitization of PANs may lead to therapies that block inappropriate chronic signals at their source, decreasing drivers of peripheral & central wind-up, yet leaving defensive nociceptive and brain functions unperturbed. This article reviews this evidence, focusing on how ATP sensitization of PANs in visceral “hollow” organs primes them to chronic discomfort, irritation & pain (symptoms) as well as exacerbated autonomic reflexes (signs), & how the use of isolated organ-nerve preparations has revealed this mechanism. Urinary & airways systems share many features: dependence on continuous afferent traffic to brainstem centers to coordinate efferent autonomic outflow; loss of descending inhibitory influence in functional & sensory disorders; dependence on ATP in mediating sensory responses to diverse mechanical and chemical stimuli; a mechanistically overlapping array of existing medicines for pathological conditions. These similarities may also play out in terms of future treatment of signs & symptoms, in the potential for benefit of P2X3 antagonists.